PENGABDIAN KEPADA MASYARAKAT (PKM) KETAHANAN PANGAN PEDESAAN KERTHALANGU DENPASAR TIMUR - I Nyoman Winyana; Ni Made Indah Resiyana Putri (JURNAL SEWAKA BHAKTI, 2021)
Community service is one of the important commitments made by universities in the context of blending in with the community. The existence of academics in the development of rural communities is at the same time a measure of the existence of universities in collaborating with rural communities. One form of PKM carried out by the Unhi campus community in 2021 is to build a village to care for the earth. Through the thematic KKN 2021, namely the village of kala Tatwa 'Ausadhining Bumi' which means glorifying plants on earth with the concept of "kala patra village or mawacara village". The 2021 KKN is carried out with a slightly different method than before. This is because during the pandemic period, it is still not possible to have face-to-face meetings, in addition to complying with health porkes. In fact, important meetings also require face-to-face activities, only that the treatment is more adapted to the COVID-19 health regulations. This PKM focuses on the important role of maintaining food security at the government and community levels. Food management carried out in the community of Kerthalangu village is important for KKN 2021 participants, not only as a learning discourse but also expected to be able to contribute to the community to give birth to new things in the field of food security